ABSORPTION OF NITROGEN OXIDES INTO SODIUM HYDROXIDE SOLUTION IN A PACKED COLUMN: EFFECT OF GAS FLOWRATE AND TEMPERATURE - Katima, J. H. Y.; Azapagic, A.; Handley, D. (Tanzania Journal of Engineering and Technology, 2018)
Abstract